The supercooling point depression is the leading cold tolerance strategy for the variegated ladybug, [Hippodamia variegata (Goezel)] - Khabir, Mahsa; Izadi, Hamzeh; Mahdian, Kamran (Frontiers in Physiology, 2023)
The variegated ladybug, Hippodamia variegata is one of the most effective predators of various pests that hibernate as adult beetles. During the overwintering period from April 2021 to March 2022, we examined the supercooling point (SCP), cold tolerance, and physiological adaptations of beetles in Kerman, Iran. The beetles exhibited their greatest cold tolerance (63.4% after 24 hours at -5°C) when their SCP was lowest (-23.2 ℃). Conversely, from April to October 2021, the SCP reached its peak (approximately -13.0 °C), while cold tolerance was at its lowest level, (6.7% after 24 hours at -5°C). Cryoprotectant content (trehalose, glycerol, and glucose) was at its highest level in September (11.15, 10.82, and 6.31 mg/g, respectively). The critical thermal minimum (CTmin) reached its lowest point of -2.2 °C in January and February. The lowest point of the lower lethal temperature (LLT) coincided with the lowest level of the SCP and the highest level of cold tolerance (in February, LT50=-5.3 °C, SCP= -23.2 °C, and survival=77.78% at -4 °C/24 hours). Chill-coma recovery time (CCRT) was examined at five different temperatures and two different exposure durations. The CCRT increased with a decrease in exposure temperature and time (68.0 seconds at -2 °C after 2 hours and 102.0 seconds at -2 °C after 4 hours). As the majority of the overwintering beetle's mortality occurred at temperatures significantly higher than SCP, the adults of H. variegata are chill-susceptible insects that primarily rely on a depressed supercooling point to cope with unfavorable conditions during the overwintering period.